Exhibition Note: Lines in the Ice at the British Library - Hatfield, Philip (Scientia Canadensis, 2015)
During the winter of 2014-15 the British Library ran a medium-sized exhibition in its Entrance Hall Gallery, Lines in the Ice: Seeking the Northwest Passage. Fortuitously benefiting from news in the summer of 2014 about the location of HMS Erebus, one of the ships from the fateful expedition of Sir John Franklin, the exhibition sought to take a long view of the history of polar exploration, particularly in the Canadian Arctic. In so doing, the aim of the exhibition was to explore the circumstances which have maintained European and North American interest in the Arctic, from trade to resources and geopolitics. The exhibition sought to ask how this has developed and what effect it has had on the societies of the explorers and the indigenous peoples of the Arctic. Within this historical narrative, science, innovation and technology played an important role. This note considers how the exhibition developed our understanding of the historic and contemporary significance of science and its practice in the Arctic.